السياسات الحكومية لترقية الإنتاج الوطني والأداة الوطنية للإنتاج في قانون الصفقات العمومية في الجزائر - وافية تميمي; نور مصوبر (My University, 2025)
Abstract: This study evaluates the effectiveness of governmental policies in Algeria aimed at promoting national production, with a focus on Law No. 23-12 and the role of the National Production Tool as a technical mechanism for assessing the national integration rate in public procurement contracts. The study starts from the premise that public procurement is not merely a regulatory tool, but a strategic instrument to support the local economy and reinforce the principle of national preference, while analyzing the impact of these policies on the industrial sector, employment, and innovation. The study concludes that these policies have yielded positive effects, such as stimulating local production and technology, but also negative repercussions, including undermining the principle of contractual equality and reducing the attractiveness of foreign investment. Therefore, the success of these policies depends on maintaining a balance between protecting national production and ensuring fair competition, while strengthening oversight mechanisms and institutional support. ......................... الملخص : تتناول هذه الدراسة تقييم فعالية السياسات الحكومية في الجزائر لترقية الإنتاج الوطني، من خلال التركيز على القانون رقم 23-12 ودور الأداة الوطنية للإنتاج كوسيلة تقنية لتقدير نسبة الإدماج الوطني في الصفقات العمومية، تنطلق الدراسة من اعتبار الصفقات العمومية وسيلة استراتيجية لدعم الاقتصاد المحلي وتكريس مبدأ الأفضلية الوطنية، مع تحليل لأثر هذه السياسات على القطاع الصناعي، والتشغيل، والابتكار. وقد خلُصت الدراسة إلى أن لهذه السياسات آثارًا إيجابية كتحفيز الإنتاج المحلي والتكنولوجيا، وأخرى سلبية كالإخلال بمبدأ المساواة التعاقدية وتقليص جاذبية الاستثمار الأجنبي. ومن ثم، فإن نجاحها يظل مرهونًا بوجود توازن بين حماية الإنتاج الوطني وضمان المنافسة، وتعزيز آليات الرقابة والمرافقة المؤسساتية. ........................ Résumé : La présente étude évalue l'efficacité des politiques publiques en Algérie en matière de promotion de la production nationale, en mettant l'accent sur la loi n° 23-12 et le rôle de l'outil national de production en tant qu'instrument technique d'évaluation du taux d'intégration nationale dans les marchés publics. L'étude part du postulat que les marchés publics constituent un levier stratégique de soutien à l'économie locale et de consécration du principe de la préférence nationale, tout en analysant l'impact de ces politiques sur le secteur industriel, l'emploi et l'innovation. L'étude conclut que ces politiques ont des effets positifs, tels que la stimulation de la production locale et de la technologie, mais également des effets négatifs, notamment une atteinte au principe d'égalité contractuelle et une réduction de l'attractivité de l'investissement étranger. Ainsi, leur succès reste tributaire de l'établissement d’un équilibre entre la protection de la production nationale et la garantie de la concurrence, tout en renforçant les mécanismes de contrôle et d’accompagnement institutionnel.
Keywords: Keywords: Government policies; national production; public procurement; Law 23-12; competitiveness.; الكلمات المفتاحية: السياسات الحكومية، الإنتاج الوطني، الصفقات العمومية، القانون 23-12، التنافسية.; Mots-clés : La politique du gouvernement; production nationale; marchés publics; loi 23-12; compétitivité.